2014
DOI: 10.1142/s2010007814500018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on the Indian Economy: Evidence From Food Grain Yields

Abstract: We analyse the effects of rainfall and temperature on yields of paddy and millets (pearl millet and sorghum) in India for the period 1966-1999, at the district level. Unlike other studies, we control for fertiliser use and irrigation. We find that paddy (India's leading food crop) is sensitive to the climate variables but also to fertiliser use and irrigation. Millets are less affected by climate variables although sorghum shows some sensitivity to temperature. Our results have important implications for how I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 22 publications
2
36
1
Order By: Relevance
“…This implies that higher rainfall and maximum temperature would mean lower the rice yield rates. The rice results are not consistent with Gupta et al () but more or less similar with Birthal et al (). The reason for not getting similar results might be the different data series and time periods.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…This implies that higher rainfall and maximum temperature would mean lower the rice yield rates. The rice results are not consistent with Gupta et al () but more or less similar with Birthal et al (). The reason for not getting similar results might be the different data series and time periods.…”
Section: Resultscontrasting
confidence: 69%
“…Using these methods, several studies have assessed the effect of weather change on crop output across the world (for instance see Sarker et al, ; Agba et al, ; Zhang, Zhang, & Chen, ; Sbaouelgi, ; Attiaoui & Boufateh, ). Some of the studies employing the econometric models to examine effects of weather variation on crop productivity in India include Guiteras (), Moorthy, Buermann, and Rajagopal (), Barnwal and Kotani (), Gupta et al (), Birthal et al (), Farook and Kannan (), Nath and Mandal (), and Pal and Mitra (). Lastly, the overview of the literature reported that changes in climate have an adverse effect on food and non‐food production.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly we have taken only the top cultivating districts of the respective crops for our final analysis. 7 Srikanth Gupta et al (2014) created crop specific fertilizer intake by dividing district-level NKP consumption by the gross cropped area of all crops grown in the district and attributed identical fertilizer consumption to all crops. However this is not practically valid given that the fertilizer intake of different crops differs significantly.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis done over a period of 40 years concludes that in contrast to its attenuation of precipitation shocks, irrigation mitigates the impact of increased seasonal heat exposure only partially (in the case of wheat), while it has no impact on rice as the increases in temperature turn out to drive most of the projected impact on yields. Gupta et al (2012) estimated the impact of climate change on food grain yields (rice and millets) in India using a crop-specific agricultural production function with district level panel data. The study found that higher rainfall leads to higher yield, while higher temperature leads to lower yields for rice.…”
Section: Review Of Existing Literaturementioning
confidence: 99%